A systematic overview on the use and relevance of capillaroscopy in systemic sclerosis. (November 2013) - Ingegnoli, Francesca; Gualtierotti, Roberta
Capillaroscopy is a non-invasive and safe technique that allows the detection and quantification of the early microvascular abnormalities that characterize secondary Raynaud's phenomenon. The well-established role of capillaroscopy for the early diagnosis of systemic sclerosis, its inclusion in the classification criteria, combined with its predictive value for clinical complications of the disease and its potential for monitoring disease progression and treatment response, makes nailfold capillaroscopy an important assessment in clinical practice and research. Capillaroscopy provides a unique window into the microcirculation and its application in diseases in which a microvascular component is suspected; it also may provide new insights into their pathophysiology and natural history.